Identification of Challenges concerned to the Research and Development (R&D) Mechanism in Public Sector Universities of Pakistan - Jam Muhammad Zafar (PJE, 2023)
Research and Development (R&D) mechanism at higher education is facing severe challenges that are plaguing the educational system of Pakistan. This study focuses the challenges of R&D mechanism concerned to the public sector universities. Sample of the study comprised of six hundred and ninety (690) faculty members from selected twenty-three (23) public sector universities. The study was survey and descriptive in nature.